Innovation Accounting Practices in SMEs: A Phenomenological Study - Suwandi (www.amertainstitute.com, 2023)
The accounting system is a key factor in the success of managing SMEs whose implementation has not been implemented optimally by some SMEs in Indonesia. This phenomenological study aims to find an innovative accounting model in SME business management at the Lamuru Market, Tellu Siattinge, Bone Regency – Indonesia. The subject of this research involved five business actors. Data was collected through the interview method. Triangulation of data sources is used in data management and is analyzed through data reduction, data presentation, and drawing conclusions. The results of the study found innovative accounting models applied by SMEs, including cash reports, accounts receivable reports, inventory reports, sales reports, and customer reports. Furthermore, these reports have been used in the process of preparing financial projections, evaluating business performance, and making business decisions. Following up on these findings, increasing understanding of SME accounting must be further optimized through ongoing accounting training.